THE ESSENCE OF POLITICAL CONSCIOUSNESS AND APPROACHES TO ITS STUDY FROM THE PERSPECTIVE OF POLITICAL SCIENCE (International Conference on Economics, Finance, Banking and Management, 2025)
This article analyzes the essence of the concept of political consciousness, its components, and theoretical approaches to its study in political science. The author interprets political consciousness as an important form of social consciousness and highlights it as a complex social phenomenon that expresses the individual's attitude to the political system, power, and political values. The article analyzes the methods of studying political consciousness based on liberal, Marxist, sociopsychological, and cultural approaches. It also covers the issues of the formation of political consciousness under the influence of information technologies in modern political processes.